Synthesis and biological evaluation of thieno[2,3-d]pyrimidine derivatives for anti-inflammatory, analgesic and ulcerogenic activity - El-Gazzar, Abdel-Rahman B. A. (Array, 2007)
The new products showed anti-inflammatory, analgesic, and ulcerogenic activities comparable to that of indomethacin and acetylsalicylic acid, respectively.